Methylenetetrahydrofolate reductase gene polymorphisms are associated with ischemic and hemorrhagic stroke: Dual effect of MTHFR polymorphisms C677T and A1298C - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
Hyperhomocysteinemia is an independent risk factor for ischemic stroke. The enzyme methylenetetrahydrofolate reductase (MTHFR) plays a critical role in modulating the levels of plasma homocysteine. Two polymorphisms in the MTHFR gene, C677T, A1298C result in reduced enzyme activity. The mechanisms of ischemic and hemorrhagic stroke are not well understood. Although controversial, previous studies have shown evidence of causality of both stroke subtypes in patients with methylenetetrahydrofolate reductase gene polymorphisms. Therefore, we examined whether the C677T and A1298C polymorphisms of MTHFR gene are genetic risk factors for both ischemic and hemorrhagic stroke in a Turkish Caucasian population. In a case-control study, 120 total unrelated stroke patients (92 ischemic stroke, 28 hemorrhagic stroke), and 259 healthy controls were genotyped for C677T and A1298C polymorphisms of the MTHFR gene using a PCR-RFLP based-method. The MTHFR 1298C allele (chi(2) = 8.589; P=0.014), C1298C genotype (OR = 2.544; P=0.004), and C677C/C1298C compound genotype (OR = 3.020; P = 0.001) were associated with overall stroke. The MTHFR 1298C allele (chi(2) = 11.166; P=0.004), C1298C genotype (OR=2.950; P=0.001), and C677C/C1298C compound genotype (OR=3.463, P=0.0001) were strongly associated with ischemic stroke. Interestingly however, the MTHFR 677T allele (chi(2) =6.033; P=0.049), T677T genotype (OR=3.120; P=0.014), and T677T/AI298A compound genotype (OR=4.211; P=0.002) were associated with hemorrhagic stroke. In conclusion, the C677T and A1298C polymorphisms of the MTHFR gene are genetic risk factors for hamorrhagic and ischemic stroke respectively, independent of other atherothrombotic risk factors. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: MTHFR; polymorphism; association; ischemic stroke; hemorrhagic stroke; Turkey; 677 C-T; RISK-FACTOR; PLASMA HOMOCYSTEINE; COMMON MUTATION; YOUNG-ADULTS; FACTOR-V; THERMOLABILE VARIANT; CEREBRAL INFARCTION; HYPERHOMOCYSTEINEMIA; HISTORY